Coats' disease - disease of the eye rarely encountered by pathologists - Hilda Fernandes; T Umashankar; Anto J Richie; Sunayana Hegde (Wolters Kluwer Medknow Publications, 2018)
Coats' Disease is an idiopathic condition of the eye affecting young children although it can be seen in adults. Most patients present early in life with unilateral decreased vision, strabismus or leukocoria. The most important differential diagnosis is unilateral retinoblastoma. In this study we report a case of coat's disease in an young girl, and evaluate histopathological and clinical findings.